2009
DOI: 10.1142/s0218271809014972
|View full text |Cite
|
Sign up to set email alerts
|

ENERGY CONDITIONS IN f(R) GRAVITY AND BRANS–DICKE THEORIES

Abstract: The equivalence between f (R) gravity and scalar-tensor theories is invoked to study the null, strong, weak and dominant energy conditions in Brans-Dicke theory. We consider the validity of the energy conditions in Brans-Dicke theory by invoking the energy conditions derived from a generic f (R) theory. The parameters involved are shown to be consistent with an accelerated expanding universe.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 14 publications
0
48
0
3
Order By: Relevance
“…Phantom field potential (Santos and Alcaniz 2005), expansion history of the universe (Visser 1997a(Visser , 1997bSantos et al 2006Santos et al , 2007aSen andScherrer 2008, 2007b) and evolution of the deceleration parameter (Gong et al 2007;Gong and Wang 2007) have been investigated using classical energy conditions of general relativity. Energy conditions in the context of f (R) gravity have been derived in Santos et al (2007c) and following the formalism developed in Santos et al (2007c), several authors have studied some cosmological issues in modified f (R) gravity from this point of view (see for example Santos et al 2010;Atazadeh et al 2009). Also, appropriate energy conditions for the f (R) gravity non-minimally coupled with matter Lagrangian has been investigated in Bertolami and Sequeira (2009).…”
Section: ; Lobo 2008; Capozziello and Francaviglia 2008 For Reviementioning
confidence: 99%
“…Phantom field potential (Santos and Alcaniz 2005), expansion history of the universe (Visser 1997a(Visser , 1997bSantos et al 2006Santos et al , 2007aSen andScherrer 2008, 2007b) and evolution of the deceleration parameter (Gong et al 2007;Gong and Wang 2007) have been investigated using classical energy conditions of general relativity. Energy conditions in the context of f (R) gravity have been derived in Santos et al (2007c) and following the formalism developed in Santos et al (2007c), several authors have studied some cosmological issues in modified f (R) gravity from this point of view (see for example Santos et al 2010;Atazadeh et al 2009). Also, appropriate energy conditions for the f (R) gravity non-minimally coupled with matter Lagrangian has been investigated in Bertolami and Sequeira (2009).…”
Section: ; Lobo 2008; Capozziello and Francaviglia 2008 For Reviementioning
confidence: 99%
“…Some of the literature review of ECs were discussed by using the classical ECs of general relativity (GR) like the phantom fields potential [46], the history of expanding universe [47][48][49][50][51][52] and the pattern movement of deceleration parameters [53,54]. The various expression for ECs are derived in f (R) gravity [55] and using these formalism and techniques, some authors have pointed out some issues (cosmological) in f (R) gravity [56][57][58]. The general formalism for ECs are derived in f (G) gravity by García et al [59].…”
Section: Introductionmentioning
confidence: 99%
“…The energy conditions have been investigated in different modified theories of gravity like f (R) gravity, BransDicke theory, f (G) gravity, and generalized teleparallel theory [22][23][24][25]. Banijamali et al [26] investigated the energy conditions for non-minimally coupling f (G) theory with L m and found that the WEC is satisfied for specific viable f (G) models.…”
Section: Introductionmentioning
confidence: 99%